Lack of Purpose and Unity: Hannibal’s Failures, Carthage’s Doom (2015)
Hannibal Barca, the son of Hamilcar Barca has been described by several Classical and modern authors as one of the greatest war strategists who ever lived. He fought and won several battles against the Roman State which at the time was the superpower in Italy and her environs. In spite of Hannibal's skills and strategies, Carthage could not annihilate Rome. This paper aims to examine the rationale that instigated Hannibal's failure to deal a decisive and crushing blow on the Roman State. The paper argues that the Carthaginian government's unresponsiveness towards Hannibal caused his failure. It continues to state that because Carthage refused to nurture and maintain the offensive realism stance, she was not motivated to consolidate Hannibal's victories in once allied territories of Rome now subdued by Hannibal; Carthage was also not motivated to send troops and resources to Hannibal which he needed to deal a crushing defeat on Rome. Consequently, Hannibal's failures translated to Carthage's doom. Thus, in 202 BC, Hannibal was defeated by Scipio Africanus. And again, after the Third Punic War of 149-146 BC, Carthage was destroyed and razed to the ground by Rome. Further studies that may examine Rome's strategies and tactics against enemy states are recommended